Highlights of the Chinese exposure factors handbook (adults) - Duan, Xiaoli (Museum meanings, 2015)
The Chinese Research Academy of Environmental Sciences (CRAES) has conducted the Environmental exposure related activity pattern research of Chinese population (Adults). Exposure Factors Handbook of Chinese Population (Adults) was compiled based on the results from this study. Highlights of the Chinese Exposure Factors Handbook is a brief introduction to the content of Exposure Factors Handbook of Chinese Population (Adults). In each chapter, definitions, possible influence factors, and survey methods have been introduced, followed by recommended values for urban/rural areas, different genders, age groups and regions with information of mean, median and P5, P25, P75, P95 values. With the abundant data and tables, readers are provided with an accessible and comprehensive overview of Chinese exposure factors.